(untitled) (Medico Legal Update, 2020)
Background/Objectives: The purpose of the study was to identify factors influencing successful aging in middle-aged women. Method/Statistical Analysis: The subjects of this study were 298middle-aged women living in 4 cities. The data were collected through structured questionnaire and analyzed using descriptivestatistics, t-test, ANOVA, Pearson correlations, Spearman correlations and multiple regressionanalysis with the SPSS/WIN 21.0 program. Findings: As a result of regression analysis using self-efficacy, self-achievement and aging anxiety as independent variables, factors affecting successful aging were self-efficacy and aging anxiety. Their explanatory power is 16.8%. Aging anxiety was found to have the most significant influence on the degree of successful aging. Improvements/Applications: Thisstudy shows that self-efficacy and aging anxiety have important effects on successful aging in middle-aged women. In addition, middle aged women learned that nursing knowledge needs to be accumulated and researched to increase self-efficacy or to reduce anxiety about aging.